Development of Multicultural-Based School Organizations in Border Regions: A Systematic Literature Review of the Strategic Role of School Principals - Zulfa Himawati; Mada Sutapa (Green Publisher Indonesia, 2026)
Border regions in Indonesia are characterized by high levels of cultural, ethnic, linguistic, and religious diversity, creating both opportunities and challenges for educational development. Schools in these areas play a crucial role in fostering social cohesion, tolerance, and national identity through multicultural education. This study aims to analyze the strategic role of school principals in developing multicultural-based school organizations in border regions and to identify leadership practices that support inclusive and adaptive educational environments. The research employed a Systematic Literature Review (SLR) approach based on the PRISMA framework. A total of ten relevant articles published between 2020 and 2025 from accredited national journals and reputable international journals indexed in Scopus and SINTA were systematically selected and analyzed. The findings revealed three major themes. First, school principals act as transformative leaders who promote inclusive school cultures by integrating multicultural values into learning and extracurricular activities. Second, principals strengthen collaboration with local communities, parents, and cultural leaders to ensure that educational practices reflect local needs and values. Third, principals encourage curriculum innovation by incorporating local wisdom and cultural diversity into teaching and learning processes. The study concludes that the success of multicultural education in border regions largely depends on the leadership capacity of school principals to manage diversity, foster participation, and implement context-responsive educational strategies. These findings provide valuable insights for policymakers and educational practitioners seeking to strengthen inclusive education in culturally diverse regions.